Pseudosymmetric Almost \(α\)-Cosymplectic \((κ,μ, u)\)-Spaces Admitting Einstein Solitons - Atceken, Mehmet; Mert, Tugba; Uygun, Pakize (Communications in Mathematics and Applications, 2024)
This paper attempts to characterize cases of an almost \(α\)-cosymplectic \((κ,μ, u)\)-space admitting Einstein sloitons to be concircular Ricci pseudosymmetry, projective Ricci pseudosymmetry, \(W_1\)-curvature and the \(W_2\)-curvature Ricci pseudo symmetric.